1990
DOI: 10.1200/jco.1990.8.9.1483
|View full text |Cite
|
Sign up to set email alerts
|

Two months of doxorubicin-cyclophosphamide with and without interval reinduction therapy compared with 6 months of cyclophosphamide, methotrexate, and fluorouracil in positive-node breast cancer patients with tamoxifen-nonresponsive tumors: results from the National Surgical Adjuvant Breast and Bowel Project B-15.

Abstract: The National Surgical Adjuvant Breast and Bowel Project (NSABP) implemented protocol B-15 to compare 2 months of Adriamycin (doxorubicin; Adria Laboratories, Columbus, OH) and cyclophosphamide (AC) with 6 months of conventional cyclophosphamide, methotrexate, and fluorouracil (CMF) in patients with breast cancer nonresponsive to tamoxifen (TAM, T). A second aim was to determine whether AC followed in 6 months by intravenous (IV) CMF was more effective than AC without reinduction therapy. Through 3 years of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
1
10

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 583 publications
(208 citation statements)
references
References 14 publications
10
187
1
10
Order By: Relevance
“…This observation is in agreement with data reported in the literature showing that an ANC o1.5 Â 10 9 l À1 at the onset of chemotherapy was not convincingly associated with an increased risk of febrile neutropaenia (Greil and Jost, 2005). Previously, the National Surgical Adjuvant Breast and Bowel Project B-15 and B-16 trials showed that the reintroduction of chemotherapy with ANC ranging between 1.0 and 1.5 Â 10 9 l À1 was possible (Fisher et al, 1990a, b). In a recent retrospective study involving Hodgkin's lymphoma patients, the ABVD (adriamycin, bleomycin, vinblastine, and dacarbazine) administration irrespective of granulocyte counts allowed the treatment to be given at full dose without delays or significant number of infective episodes (Boleti and Mead, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…This observation is in agreement with data reported in the literature showing that an ANC o1.5 Â 10 9 l À1 at the onset of chemotherapy was not convincingly associated with an increased risk of febrile neutropaenia (Greil and Jost, 2005). Previously, the National Surgical Adjuvant Breast and Bowel Project B-15 and B-16 trials showed that the reintroduction of chemotherapy with ANC ranging between 1.0 and 1.5 Â 10 9 l À1 was possible (Fisher et al, 1990a, b). In a recent retrospective study involving Hodgkin's lymphoma patients, the ABVD (adriamycin, bleomycin, vinblastine, and dacarbazine) administration irrespective of granulocyte counts allowed the treatment to be given at full dose without delays or significant number of infective episodes (Boleti and Mead, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, anthracyclines have mainly been administered to patients with non-Hodgkin's lymphoma and breast cancer (Table 3). Although it is generally accepted that CHOP is an immunosuppressive regimen, only 4% of Western breast cancer patients receiving AC developed severe immunosuppression (Fisher et al, 1990). However, recent data from Chinese breast cancer patient population revealed the corresponding figure to be as high as 77% (Ma et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There was no family history of breast cancer in any patient. Twelve patients [12] had undergone modified radical mastectomy (MRM) outside and had been referred to our hospital for further management. Five patients had metastatic disease at presentation of which three had bone metastasis (one patient had solitary vertebral metastasis and other two had multiple bony metastases), two had lung metastasis of which one had pleuritis carcinomatosis (one patient had bone metastases also), and one had liver metastases.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from invasive ductal carcinoma, medullary, metaplastic, secretory, pleomorphic lobular carcinomas, adenoid cystic carcinomas etc., also belong to triple negative tumours. The main characteristics of triple negative breast cancers are they are frequent in younger women (<50 years), more frequent in AfricanAmerican women, present as interval cancers, highly chemosensitive [12,13], weak association between tumour size and lymph node metastases, more aggressive, higher chance of brain metastases, high chance of recurrence during 1 st and 3 rd year and shorter survival following first metastatic event when compared to other subtypes.…”
Section: Introductionmentioning
confidence: 99%